2019
DOI: 10.30564/jiep.v2i2and3.1006
|View full text |Cite
|
Sign up to set email alerts
|

Implementing the Curriculum and Assessment Policy Statement: A Case Study of the Vhembe West District, South Africa

Abstract: This qualitative study was undertaken to investigate how district officials implemented Curriculum and Assessment Policy Statement in the Vhembe West District in South Africa. Interview data were collected and used for themes identification. The study identified the following challenges that the district officials experienced as they performed their duties: insufficient resources, lack of finances to buy learning and teaching support materials, infrastructure failures, the district’s inadequate support to scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…However, a number of prior inquiries have verified that the district's insufficient finances prevent it from providing curriculum consultants with the necessary help. This outcome is consistent with the research of several other scholars, such as Rammbuda (2019), who assert that the district does not have the resources to buy instructional aids.…”
Section: Structural Equation Modellingsupporting
confidence: 91%
See 1 more Smart Citation
“…However, a number of prior inquiries have verified that the district's insufficient finances prevent it from providing curriculum consultants with the necessary help. This outcome is consistent with the research of several other scholars, such as Rammbuda (2019), who assert that the district does not have the resources to buy instructional aids.…”
Section: Structural Equation Modellingsupporting
confidence: 91%
“…In addition, Beukes (2017) and West and Meier (2020) notice that there are two serious issues: insufficient funding and improper use of public funds. Supporting the arguments made by Beukes (2017), West and Meier (2020), and Rammbuda (2019) above, McLennan et al (2017 claimed that curriculum advisors only visited schools once a year to assess how far along teachers and principals were with the curriculum because districts lack the resources or funding to visit schools. The findings of this study concur with Blignaut (2020) who contends that 'curriculum and pedagogic change will only succeed if we embrace new ways of viewing knowledge and as well as embracing multiple knowledge traditions' in order to overcome this theorising difficulty facing curriculum studies in South Africa.…”
Section: Structural Equation Modellingmentioning
confidence: 98%
“…The department has made an effort to keep teachers aware about the requirements of the curriculum change. The ability of the South African educational system to offer suitable professional support to schools, however, has a dismal track record, according to Rammbuda (2019). Teachers find it challenging to successfully implement curriculum changes in overcrowded classrooms.…”
Section: Challenges Faced By Curriculum Advisorsmentioning
confidence: 99%
“…Bantwini (2015) reveals the lack of support for schools by districts in the South African context. Again, Rammbuda (2019) indicates that the capacity of the South African education system to provide appropriate professional support to schools has a poor track record. Data gathered also showed that workshops were not given enough help.…”
Section: Theme 4: Inadequate District Support For Curriculum Advisorsmentioning
confidence: 99%
See 1 more Smart Citation